RENDERING OF “SADOQAT” AND “LOYALTY” IN UZBEK–ENGLISH AND ENGLISH–UZBEK BILINGUAL DICTIONARIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
Loyalty is a central ethical and sociocultural value in both Uzbek and English speech communities, yet its representation in bilingual lexicographic sources remains complex and problematic (Adamska-Sałaciak, 2010). In Uzbek, the key lexeme “sadoqat” is intertwined with a broader cluster of value-charged units such as “vafo, ” “sodiqlik, ” and “vafodorlik,” while in English the item “loyalty” appears alongside near-synonyms like “faithfulness,” “allegiance,” “devotion,” and “fidelity”. Against this background, the present article investigates how “sadoqat” and “loyalty” are presented in Uzbek–English and English–Uzbek bilingual dictionaries, focusing on types of equivalence, the extent of semantic coverage, and the cultural-pragmatic adequacy of the proposed translation equivalents (Baker, 2018).